Comparison of creatinine- and cystatin C-based definitions of acute kidney injury in neonates with congenital diaphragmatic hernia - Leyens, Judith; Gerschlauer, Jana; Berg, Christoph; Strizek, Brigitte; Mueller, Andreas; Kipfmüller, Florian; Schroeder, Lukas (Pediatric nephrology, 2026)
Acute kidney injury (AKI) is a frequent complication in critically ill neonates and is associated with adverse outcomes. Infants with congenital diaphragmatic hernia (CDH) are particularly vulnerable due to pulmonary hypoplasia, hemodynamic instability, and exposure to nephrotoxic agents.